Pengaruh Viral Marketing dan Fear of Missing Out (FoMO) Terhadap Keputusan Penggunaan Jasa Pada Self Photo Studio Anxietive Kota Pekanbaru - Helda Rizki Amalia; Rosmayani Rosmayani (SYNERGY: Jurnal Bisnis dan Manajemen, 2025)
This study aims to examine the extent to which viral marketing and Fear of Missing Out (FoMO) influence the decision to use services at Anxietive self-photo studio in Pekanbaru. The research employs a quantitative approach. The sample was selected using purposive sampling with total of 100 respondents, data were collected through observation, interviews, questionnaires, documentation, and literature review. The data were analyzed usis SPSS sofwere by condusting several tests, including validity and reliability tests, classical assumption tests {normality, multicollinearity, and heteroscedasticity), multiple linear regression analysis, t-test, F-tests, and the coefficient of determination (R2). The result show that viral marketing and fear of missing out (FoMO) have a significant simultaneous effect on the decision to use services. Furthermore, the coefficient of determination (R2) indicates that viral marketing and fear of missing out (FoMO) strongly influence the decisions to use services at Anxietive self-photo studio in Pekanbaru